Offline Error Detection in MEDA-Based Digital Microfluidic Biochips Using Oscillation-Based Testing Methodology - Shukla, V. (Springer New York LLC, 2017)
Digital microfluidics is an emerging class of lab-on-a-chip system. Reliability is a critical performance parameter as these biochips are employed in various safety-critical biomedical applications. With the introduction of highly scalable, reconfigurable and field programmable Micro-Electrode-Dot-Array (MEDA) architecture, the limitation of conventional DMFBs in varying the droplet size/volume in fine grain manner has been resolved. However, the MEDA-based biochips must be adequately tested upon fabrication to guarantee the correctness of bioassays. In this work, an offline testing approach based on Oscillation-Based Testing (OBT) methodology is presented for MEDA-based digital microfluidic biochips. Various simulations were performed for droplet-electrode short fault model involving single and multiple micro-electrodes. Furthermore, the loss of droplet volume due to the presence of defect was analyzed using COMSOL Multiphysics. The simulation results based on PSpice and COMSOL show that the proposed approach is effective for detecting defects in MEDA-based biochips. © 2017, Springer Science+Business Media, LLC.